Cold Exposure Affects Lipid Metabolism, Fatty Acids Composition and Transcription in Pig Skeletal Muscle - Xu, Ziye; Chen, Wentao; Wang, Liyi; Zhou, Yanbing; Nong, Qiuyun; Valencak, Teresa G.; Wang, Yizhen; Xie, Jintang; Shan, Tizhong (Frontiers in Physiology, 2021)
The effects of cold exposure on meat and nutritive quality of pigs remain unclear. Here, we kept finishing pigs under cold or room temperature overnight and determined the effects of cold exposure on meat quality, fatty acids composition and transcriptional changes in skeletal muscles of pigs. We found that cold exposure significantly reduced the meat colour24h and pH24h, without affecting carcass characteristics and other meat quality traits. Considerable changes were found in the proportions of individual fatty acids and the total content of saturated fatty acid, polyunsaturated fatty acids, monounsaturated fatty acid and n3-fatty acids. RNA-seq results showed upregulated fatty acid biosynthesis genes and downregulated mitochondrial beta-oxidation genes. The lipid metabolism in cold-treated longissimus dorsi muscle might be regulated by functions of the lipoprotein particle, the extracellular matrix, and the PPAR signaling pathways. Our study revealed the potential of cold exposure to regulate the lipid metabolism and fatty acid composition in skeletal muscle of farmed animals.